Traduções, adaptações, apropriações: reescrituras das peças Hamlet, Romeu e Julieta e Otelo, de William Shakespeare - Bertin, Marilise Rezende (2008)
The present thesis consists of a study on some rewritings of three plays written by William Shakespeare: Hamlet, Romeo and Juliet and Othello. Firstly, terms like translation, literal translation, free translation, rewriting, adaptation, updating, appropriation, condensation and recreation will be tackled with the purpose of understanding the process of interlingual and intralingual translations. The analysis of the theories developed by Hans J. Vermeer and Georges L. Bastin will be extremely important in order to justify and exemplify translations (adaptations) which are not so faithful and are aimed at specific types of public. The historical study of a number of French translations show how erotic, bawdy and grotesque parts of the Shakespearean texts were altered or omitted. Lastly, I analyse the bilingual adaptations of the three plays mentioned above, which I carried out with John Milton.